Parental Discipline Patterns on Children in Penjaringan Slums : Gambaran Pola Disiplin Orang Tua terhadap Anak di Kawasan Kumuh Penjaringan - Kristiani, Reneta; Lunanta, Lita Patricia (Psikologia : Jurnal Psikologi, 2019)
This research aimed to describe the discipline pattern that the parents had on their children. This research was held in slum area of Penjaringan in DKI Jakarta. Total of 154 people became the participant in this research. This was a descriptive study that wish to explore the discipline pattern that parents implemented to their children. Along with that we also explored about communication pattern and relation in family. We used questioners for information gathering and implemented observation, interview and small group discussion. To analyze the data, we used describtive statistical analysis technique and qualitative analysis. Most of the participant cared about their children. Nevertheless they implemented harsh communication style to their children.The parcitipant had a hope to be an ideal parent but did not have any idea what to do. Further research needed to be done and actions had to be implemented in order to create a healthy and fully functioning family in the slum area of Penjaringan.